The Role of Instagram in the Personal Branding Strategies of Major Streamers: A Case Study of Windah Basudara - Adelia Weebe Chandra; Amir Indrabudiman (Journal of Social Research, 2026)
This study examines the role of Instagram in the personal branding strategies of major streamers, focusing on Windah Basudara, a prominent YouTube content creator with a Diamond-Tier channel. The research aims to determine whether Instagram remains relevant for established streamers and how cross-platform branding affects audience engagement and community loyalty. A qualitative case study method was employed, including observations of Windah's Instagram feeds, stories, and reels from December 2025 to February 2026, alongside interviews with internal team members, fans, and a personal branding practitioner. Data were analyzed using triangulation and thematic interpretation, guided by Peter Montoya's eight laws of personal branding. Results indicate that Windah's Instagram strategy is community-centered, emphasizing parasocial relationships through spontaneous, authentic content, high responsiveness, and participatory charity activities. Contextual adaptation allows him to maintain core identity while adjusting visual and communication styles across platforms. His approach reinforces engagement, loyalty, and a positive public image without reliance on curated aesthetics. The study concludes that Instagram remains essential for sustaining personal branding and relational influence among established streamers. Future research should explore socio-cultural adaptations of branding theories and quantitatively measure cross-platform engagement to generalize effectiveness in diverse digital ecosystems.